Ta’zizu Daur al-Muallim ka ’Unsurin Basyari Muhimmin fi Ta’lim al-Lughah al-‘Arabiyyah li Al-Nathiqina bi Ghairiha - Ismail, Ali Mahmud al-Usmu’i; Qasb, Intishar Muhammad (Al-Wazan: Journal of Arabic Education, 2023)
The future vision of the educational systems concerned with teaching the Arabic language to non-native speakers requires basic skills that must be mastered, such as adaptation, flexibility, accommodating the rapid change in the local and global surrounding environment, the ability to convey ideas by the fastest and most accurate means, and work to develop the capabilities of the teacher and the learner in the educational and learning process, and the absorption of technological means. To develop the competence of the non-Arabic speaking learner and to promote the Arabic language and raise its level among the learners. This research is a descriptive research, and the descriptive research aims to "describe certain phenomena, events, or things, collect facts, information, and observations about them, describe their circumstances, and report their condition as they exist in reality." Many educational programs, plans, and initiatives undertaken by many educational institutions sought to advance the educational sector and strengthen teachers - specifically teachers of Arabic for non-native speakers - by raising their educational level and providing them with modern knowledge through courses, training workshops, lectures, and professional development programs to provide them with the teaching competencies they need. In teaching Arabic to non-native speakers. The content of these programs and the methods of teaching them and the evaluation used in them stems from the goals of teaching the Arabic language in general, and the goals of teaching the Arabic language to non-native speakers in particular, developing teaching methods, strategies and educational activities, developing the professional capabilities of the teacher, and strengthening his role as an important human element in teaching Arabic to non-native speakers.